Raman spectroscopy of nanomaterials synthesized on the iron meteorites surfaces. (24th October 2021) - Begunova, Anastasia; Pankrushina, Elizaveta; Yakovlev, Grigory; Kamalov, Robert; Grokhovsky, Victor
Abstract: Iron meteorites and pallasites contain a set of Fe–Ni alloys with various structural and elemental compositions. They were formed due to a very low cooling rate of about 1–10°/Myr. These alloys can be used as substrates for growing multiwalled carbon nanotubes (MWCNTs) and hematite nanowires. We used two meteorites: Chinga ataxite and the metal part of Seymchan (pallasite of the main group [PMG]). They contained an α‐(Fe, Ni) alloy with ~7 wt.% Ni, γ‐(Fe, Ni) alloy with ~40% Ni, γ‐(Fe, Ni) alloy with ~25% Ni, and two mixed structures of α‐ and γ‐alloys with micrometer‐sized phases (Seymchan) and consisting from phases 0.05–0.1 μm in size (Chinga). Alloys in meteorites are located close to each other; therefore, the influence of the regions bordering between the alloys on the synthesis of nanomaterials can be observed. We get both MWCNTs and hematite nanowires on the surface of the submicron structure of the Chinga meteorite. We obtain a straight array of hematite nanowires on the surface of the γ‐(Fe, Ni) alloy. The structural composition of the obtained nanomaterials was determined using scanning electron microscopy and Raman spectroscopy. We measured the Raman spectra of the MWCNT/hematite nanowires composite and the Raman spectra of hematite nanowires. Abstract : In our study, we obtained both hematite nanowires and carbon nanotubes using the same samples. The figure shows their spectra.